2016
DOI: 10.3390/ijerph13030349
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Determination of Polycyclic Musks in River and Wastewater by GC/MS/MS

Abstract: The separation of chiral compounds is an interesting and challenging topic in analytical chemistry, especially in environmental fields. Enantioselective degradation or bioaccumulation has been observed for several chiral pollutants. Polycyclic musks are chiral and are widely used as fragrances in a variety of personal care products such as soaps, shampoos, cosmetics and perfumes. In this study, the gas chromatographic separation of chiral polycyclic musks, 1,3,4,6,7,8-hexahydro-4,6,6,7,8,8-hexamethylcyclo-pent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge there are only three reports about the occurrence of chiral polycyclic musks (PCMs) in environmental samples as surface waters and WWTPs [139,140]. These substances are fragrances used in personal care products.…”
Section: Polycyclic Musks (Pcms)mentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge there are only three reports about the occurrence of chiral polycyclic musks (PCMs) in environmental samples as surface waters and WWTPs [139,140]. These substances are fragrances used in personal care products.…”
Section: Polycyclic Musks (Pcms)mentioning
confidence: 99%
“…Though the ER were not determined for all compounds due to their low resolution, HHCB, AHTN, AHDI and ATII showed non-racemic ER suggesting a enantioselective biodegradation during wastewater treatment [140]. Lee et al reported the occurrence of five PCMs enantiomers in river and WWTPs samples [139]. Isomers cis and trans from HHCB were found and their enantiomeric composition was nearly racemic river and in influent samples.…”
Section: Polycyclic Musks (Pcms)mentioning
confidence: 99%
“…To date, there have been a few literature reports concerning the enantioselective determination of various PCMs, and gas chromatography on a cyclodextrin‐based capillary column has most commonly been applied for such enantioseparations . Berset et al developed a specific method for the enantioseparation of five chiral PCMs and HHCB‐lactone employing an Rt‐BDEXcst capillary gas chromatography (GC) column (BGB Analytik, Anwil, Switzerland), but their results showed a very long chromatographic run time of approximately 370 min and relatively unsatisfactory resolution of the enantiomers.…”
Section: Introductionmentioning
confidence: 99%
“…19 To date, there have been a few literature reports concerning the enantioselective determination of various PCMs, and gas chromatography on a cyclodextrin-based capillary column has most commonly been applied for such enantioseparations. 1,4,16,17,20,21 Berset et al 16 were Soxhlet-extracted with dichloromethane for 72 h, then activated for 12 h at 180 and 250°C, respectively. After deactivation with 3% redistilled water, the silica gel and neutral alumina were kept in n-hexane until use.…”
Section: Introductionmentioning
confidence: 99%
“…Several instrumental methods have been developed for PCM determination, including high-performance liquid chromatography (HPLC) [ 14 ] and gas chromatography coupled with electron capture detection (GC–ECD), mass spectrometry (GC–MS) [ 15 ], or triple quadrupole tandem mass spectrometry (GC–MS/MS) [ 16 , 17 ]. GC–MS/MS can provide enhanced selectivity and sensitivity compared with conventional single quadrupole GC–MS, effectively eliminating matrix interferences.…”
Section: Introductionmentioning
confidence: 99%